Deriving Global OH Abundance and Atmospheric Lifetimes for Long‐Lived Gases: A Search for CH3CCl3 Alternatives. Issue 21 (4th November 2017) - Liang, Qing; Chipperfield, Martyn P.; Fleming, Eric L.; Abraham, N. Luke; Braesicke, Peter; Burkholder, James B.; Daniel, John S.; Dhomse, Sandip; Fraser, Paul J.; Hardiman, Steven C.; Jackman, Charles H.; Kinnison, Douglas E.; et al.
Abstract: An accurate estimate of global hydroxyl radical (OH) abundance is important for projections of air quality, climate, and stratospheric ozone recovery. As the atmospheric mixing ratios of methyl chloroform (CH3 CCl3 ) (MCF), the commonly used OH reference gas, approaches zero, it is important to find alternative approaches to infer atmospheric OH abundance and variability. The lack of global bottom‐up emission inventories is the primary obstacle in choosing a MCF alternative. We illustrate that global emissions of long‐lived trace gases can be inferred from their observed mixing ratio differences between the Northern Hemisphere (NH) and Southern Hemisphere (SH), given realistic estimates of their NH‐SH exchange time, the emission partitioning between the two hemispheres, and the NH versus SH OH abundance ratio. Using the observed long‐term trend and emissions derived from the measured hemispheric gradient, the combination of HFC‐32 (CH2 F2 ), HFC‐134a (CH2 FCF3, HFC‐152a (CH3 CHF2 ), and HCFC‐22 (CHClF2 ), instead of a single gas, will be useful as a MCF alternative to infer global and hemispheric OH abundance and trace gas lifetimes. The primary assumption on which this multispecies approach relies is that the OH lifetimes can be estimated by scaling the thermal reaction rates of a reference gas at 272 K on global and hemispheric scales. Thus, the derived hemispheric and global OH estimates are forced to reconcile the observed trends and gradient for all four compounds simultaneously. However, currently, observations of these gases from the surface networks do not provide more accurate OH abundance estimate than that from MCF. Key Points: The interhemispheric mixing ratio difference of a long‐lived gas can be used as a quantitative proxy to derive global emissions The combination of multiple species in the gradient trend‐based approach should reduce the uncertainties in global OH abundance estimate HFC‐32 and HFC‐134a, with the help of HFC‐152a and HCFC‐22, are likely the best CH3 CCl3 alternatives as atmospheric OH reference gases